IMPROVING THE VOCABULARY MASTERY THROUGH NUMBERED HEADS TOGETHER TECHNIQUE OF THE SEVENTH GRADE STUDENTS OF SMP N 5 BATURITI IN ACADEMIC YEARS 2015/2016 - Sanjaya, I.D.M.A.W.; Sudirman, -; Wedhanti, N.K. (Jurnal Pendidikan Bahasa Inggris undiksha, 2019)
This study was a classroom based action research which aimed: (1) to find out whether Numbered Heads Together technique can improve students’ vocabulary mastery, (2)to find out the response of the students toward the implementation of the strategies. This study was conducted in two cycles consisting of three sessions in each cycle. There were two kinds of data (qualitative and quantitative data) which were collected through tests, questionnaire, and writer’s diary.The result of the tests showed that the students’ vocabulary mastery was improved in each cycle. The students’ mean score was 4.63% in pretest, 6.2 in posttest 1, and improved became 7.97 in posttest 2. It can be also seen on the number of students passing the test. There were no students passed in the pretest, 2 students in the posttest 1, and 18 students in the posttest 2. The result of writer’s diary and questionnaire also showed that the students gave positive response toward the strategies. The results of the questionnaires showed that 18 (90%) of the students admitted that they really like the implementation of Numbered Heads Together technique. Moreover, 17 (85%) of the students admitted that they were motivated in learning English using Numbered Heads Together technique.  Key Words: Numbered Heads Together Technique, Vocabulary Mastery